Analysis of community older adult care facility construction and demand differentiation based on residential area and population attribute differences - Yanzhe Liu; Yaolei Wang; Guiping Guo; Tubao Yang; Tubao Yang; Yupeng Liu; Hongmei Gao; Tiejian Jiang; Xiangmin Li (Frontiers in Public Health)
Currently, China has fully entered an aging society. The construction and efficient utilization of community older adult care facilities have become urgent issues that need to be addressed. To explore the differences in the needs of older adult people in the community for older adult care services, this study selected three basic needs: life care, medical security, and cultural and entertainment, as the primary indicators of community older adult care needs. A community older adult care demand indicator system was constructed, which included three primary indicators and 11 secondary indicators. Based on the indicator system, a survey questionnaire was designed, and validity analysis was conducted using Kaiser Meyer Olkin test and Bartlett sphericity test. 490 survey questionnaires were distributed to 22 communities in Wuhan, and 447 valid questionnaires were collected, with a response rate of 91.22%. The results indicated that there were significant differences in the distribution of older adult population in different communities. Different types of residential areas and housing prices affected its construction and use. The demand for home-based older adult care services in communities varied significantly. Through analysis of variance, the type of residential area did not show significant differences in older adult bathing assistance, daytime care, mental comfort, sports activities, etc. (p > 0.05), while there were statistical differences in nighttime care, medical care, rehabilitation care, older adult canteens, chess and card entertainment, artistic activities, etc. (p < 0.05). No significant difference existed in different housing prices for daytime care, nighttime care, mental comfort, and fitness activities (p > 0.05), but there was statistical difference for rehabilitation care, medical care, chess and card entertainment, senior dining halls, and artistic activities (p < 0.05). According to logistic regression analysis, the income level, self-care ability, and education level had obvious impacts on their basic needs for life care, with OR values of 11.68, 2.621, and 1.792, respectively. This study can provide effective reference for building diversified community home-based older adult care service facilities.